Inter-limb coordination in the four competive stroke - Chollet, D.; Seifert, L. (World book of swimming: From science to performance, 2012)
In swimming, as in several sports, the performance optimization relates to capacity of swimmers to coordinate their motor actions. In alternates strokes (front crawl and backstroke), the inter-arm coordination is evaluated. The method uses the Index of Coordination (IdC) to measure the coordination of arm stroking with precise quantification of the lag time between the start of propulsion by one arm and the end of propulsion by the other, and secondly to describe how this index varies as a function of the stroking parameters (speed, stroke rate, stroke length). In simultaneous strokes the assessment of arm-leg coordination, both in butterfly stroke and in breaststroke, consists to analyse the spatial-temporal relationships between the key points defining the start and the end of the arm and the leg stroke phases. Coordination changes are function of skill level, gender, and speed. The major objective of this chapter was to present the studies about the coordination, firstly of arm stroking in alternates strokes, secondly arm to leg coordination in simultaneous strokes, thirdly the effect of skill, gender and speed on inter-limb coordination and fourthly the coordination between propulsion and breathing: effect of preferential side of breathing, coordination asymmetry, force asymmetry and handedness.